Korruptionsstrafrecht Unerforschtes Terrain und neue Wege - Zimmermann, Till (Beiträge zum Strafrecht - Contributions to Criminal Law, 2023)
Can German criminal law on corruption be improved by new regulatory models? This conference volume presents instruments from the international toolbox of criminal law against corruption that are largely unknown in Germany and examines the question of whether they should be adopted in German criminal law. The possibility of a general criminal offense of corruption, abuse of office, illicit enrichment, trading in influence (influence peddling) and concussion (extortive bribery), as well as the instrument of non-conviction-based confiscation and approaches under international criminal law are examined. With contributions by Prof. Dr. Stefanie Bock | Prof. Dr. Dr. h.c. Lothar Kuhlen | Dr. Oliver Landwehr, LL.M. Eur. | Prof. Dr. Frank Meyer, LL.M. (Yale) | Dr. Kristina Peters, M.A. | Univ. Ass. Dr. Martin Stricker | Prof. Dr. Frank Zimmermann | Prof. Dr. Till Zimmermann